Illness-related suffering and need for palliative care in Rohingya refugees and caregivers in Bangladesh: A cross-sectional study. - Megan Doherty; Liam Power; Mila Petrova; Scott Gunn; Richard Powell; Rachel Coghlan; Liz Grant; Brett Sutton; Farzana Khan (PLoS Medicine, 2020)
BACKGROUND:Despite recognition that palliative care is an essential component of any humanitarian response, serious illness-related suffering continues to be pervasive in these settings. There is very limited evidence about the need for palliative care and symptom relief to guide the implementation of programs to alleviate the burden of serious illness-related suffering in these settings. A basic package of essential medications and supplies can provide pain relief and palliative care; however, the practical availability of these items has not been assessed. This study aimed to describe the illness-related suffering and need for palliative care in Rohingya refugees and caregivers in Bangladesh. METHODS AND FINDINGS:Between November 20 and 24, 2017, we conducted a cross-sectional study of individuals with serious health problems (n = 156, 53% male) and caregivers (n = 155, 69% female) living in Rohingya refugee camps in Bangladesh, using convenience sampling to recruit participants at the community level (i.e., going house to house to identify eligible individuals). The serious health problems, recent healthcare experiences, need for medications and medical supplies, and basic needs of participants were explored through interviews with trained Rohingya community members, using an interview guide that had been piloted with Rohingya individuals to ensure it reflected the specificities of their refugee experience and culture. The most common diagnoses were significant physical disabilities (n = 100, 64.1%), treatment-resistant tuberculosis (TB) (n = 32, 20.5%), cancer (n = 15, 9.6%), and HIV infection (n = 3, 1.9%). Many individuals with serious health problems were experiencing significant pain (62%, n = 96), and pain treatments were largely ineffective (70%, n = 58). The average age was 44.8 years (range 2-100 years) for those with serious health problems and 34.9 years (range 8-75 years) for caregivers. Caregivers reported providing an average of 13.8 hours of care per day. Sleep difficulties (87.1%, n = 108), lack of appetite (58.1%, n = 72), and lack of pleasure in life (53.2%, n = 66) were the most commonly reported problems related to the caregiving role. The main limitations of this study were the use of convenience sampling and closed-ended interview questioning. CONCLUSIONS:In this study we found that many individuals with serious health problems experienced significant physical, emotional, and social suffering due to a lack of access to pain and symptom relief and other essential components of palliative care. Humanitarian responses should develop and incorporate palliative care and symptom relief strategies that address the needs of all people with serious illness-related suffering and their caregivers.